A pediatric case of Meckel diverticulum with uncommon presentation showing no lower gastrointestinal bleeding - Sanaz Mehrabani; Soheil Osia (MDPI AG, 2017)
Meckel's diverticulum (MD) is the most common congenital abnormality of the gastrointestinal tract. Painless intestinal hemorrhage is a frequently occurring complication that relates to MD in children. Bowel obstruction is a rare complication of MD in children. We report on the case of a fouryear old male child who presented with abdominal pain and hematemesis. Finally, bowel obstruction due to MD was confirmed at surgery.